Thermosensitive hydrogel for in situ-controlled methotrexate delivery - Carrillo Castillo, Teresa Darlen; Castro Carmona, Javier Servando; Luna Velasco, Antonia; Zaragoza Contreras, erasmo armando (2021)
Abstract: Methotrexate (MTX) is widely used for the treatment of various types of cancer; however, it has drawbacks such as low solubility, lack of selectivity, premature degradation, and side effects. To solve these weaknesses, a hydrogel with the ability to contain and release MTX under physiological conditionswithout burst release was synthesized. The hydrogel was fabricated with a poly(ɛ-caprolactone)-bpoly( ethylene glycol)-b-poly(ɛ-caprolactone) (PCL–PEG–PCL) triblock copolymer, synthesized by ring-opening polymerization. The characterizations by proton nuclear magnetic resonance spectroscopy and Fourier-transform infrared spectrometry confirmed the copolymer assembly, whereas the molecular weight analysis validated the PCL2000–PEG1000–PCL2000 structure. The copolymer aqueous solution exhibited sol–gel phase transition at 37°C and injection capacity. The hydrogel supported a load of 1,000 μg MTX·mL−1, showing a gradual and sustained release profile of the drug for 14 days, with a delivery up to 92% at pH 6.7. The cytotoxicity of the MTX-loaded hydrogel was performed by the methyl thiazole tetrazolium assay, showing a mean inhibitory concentration of 50% of MCF-7 cells (IC50) at 43 μg MTX·mL−1.